Analisis Nilai Profil Pelajar Pancasila dalam Cerita Pendek Senyum Karyamin dan Tawa Gadis Padang Sampah Karya Ahmad Tohari - Syaidah, Syaidah; Handayani, Nanik; Mirna, Wa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
The library approach is the approach used in this descriptive research. The data sources used are Two short stories by Ahmad Tohari entitled Smile Karyamin and Tawa Gadis Padang Garbage which are the data sources of this research, while the data are in the form of words, phrases, and clauses that contain PPP values through prologue, monologue, or dialogue in short stories. Reading, taking notes, and documenting are data collection techniques. To analyze the data obtained, the researchers conducted reduction, presentation, and drawing conclusions. Found 105 data containing character values which are described as follows. a) Dimensions of faith, piety to TYME, and noble character which contains 52 values consisting of religious values, honesty, fairness, humility, empathy, social care, generosity, compassion, responsibility, care for the environment, and likes to help. b) The global diversity dimension which contains five values, namely mutual respect. c) The mutual cooperation dimension contains 12 values, namely cooperation, mutual cooperation, and sharing. d) The independent dimension which contains seven values of responsibility. e) The critical reasoning dimension contains 22 values consisting of curiosity and hard work. f) Creative dimension which contains four values.